A vulnerability scanning scheme based on attack graph for smart grid industrial control system. Issue 1 (January 2021) - Xu, Kai; Wang, Xiangqun; Xu, Hao; Dong, Ning; Han, Meng; Zhou, Xianfei
Abstract: As the core of national development, smart grid industrial control system has extremely high security requirements. However, due to the existence of many security vulnerabilities and lack of effective security protection measures, it is vulnerable to attacks from the Internet. Therefore, the vulnerability scanning of smart grid ICS has important research significance. Aiming at the problem that the smart grid ICS cannot bear the heavy system overhead, a safe and low system overhead vulnerability scanning scheme for smart grid ICS is innovatively proposed. This scheme introduces attack graph technology into vulnerability scanning, proposes vulnerability risk assessment indicators, and flexibly designs the scanning cycle according to the generated attack graph. Simulation results show that this scheme effectively reduces scanning costs while ensuring system security, and is better adapted to smart grid ICS.